Evolução cromossômica em Osteoglossiformes (Teleostei, Osteoglossomorpha) : uma abordagem intercontinental na família Notopteridae - Barby, Felipe Faix (2018)
The order Osteoglossiformes represent one of the most basal groups among the Teleosteos. These fishes live exclusively on freshwater environments and are characterized by the presence of a bonytongue. The group is a good model for evolutive studies due the presence of alive representatives in all continental lands localized on south hemisphere (except the Antarctic continent) even with a gondwanica origin (allowing to perform inferences about vicariant/dispersal events). The members of the Notopteridae family are distributed throughout the African and Asian (in tropical region) continents. In order to explain the distribution of the Asian biota that has close relations with the species present in Africa, the hypothesis "Out-of-India" was proposed. The idea in this hypothesis is that the lineages previously present in Gondwana reached Asia through the continental drift of the Indian subcontinent. This idea was considered the better explanation for the distribution of notopterids during a long time, but recent molecular data disclose disagreements between the geological times of tectonic drift and molecular divergence. In this context, we perform chromosomal and molecular approaches to infer about the group's diversity in relation to its biogeography. Chromosomal approaches involved classical banding techniques as well as FISH assays using repetitive DNA probes, chromosome painting and CGH; while the molecular approach was performed through the analysis of allelic sequences containing SNP polymorphisms obtained by the DArTseq genotyping technique, which involves next generation sequencing technology. The results of cytogenetic data pointed a diploid number variation in two of the seven species here studied, and also was verified variations for the distribution of the rDNA 18S and rDNA 5S markers for three species. This variation for the karyotype structure in the family was better evidenced by the CGH results, in which few chromosomal segments were shared between the intergeneric crossings assays. Indeed, these chromosomal variations was expected due the ancient divergent time in scale of tens of millions years ago between the lineages. The chromosome painting results showed a shared segment in all the seven species, pointing a possible linkage site that was also in the ancestor of the group. The PCA analysis of the polymorphisms obtained by DArTseq grouped the species according to their geographic distribution, result that was also verified by a Bayesian analysis when both chromosomal and molecular markers was combined. Thus, based on our data here obtained together with the molecular data obtained in the literature, we infer about the possibility of a gene flow occurring even after the separation of the African and Indian continental masses, discussing possibilities of the existence of temporary bridges linking Africa to the subcontinent Indian Ocean through the island of Madagascar and the Seychelles archipelago. Indeed, the existence of gene flow through temporary bridges in some moment linking the Africa to islands present in the sea localized on the African east coast is discussed in several groups of limited dispersion, which gave rise to an alternative hypothesis to "Out-of-India", called "Lemurian-step-stones". This approach from the point of view of "Lemurian-step-stones" is the first one carried out on freshwater fish.